The problem-solving method: Efficacy for learning and motivation in the field of physical education - Ezeddine, Ghaith; Souissi, Nafaa; Masmoudi, Liwa; Trabelsi, Khaled; Puce, Luca; Clark, Cain C. T.; Bragazzi, Nicola Luigi; Mrayah, Maher (Frontiers in Psychology, 2023)
The main purpose of this study was to compare the effects of the problem-solving vs. traditional method on motivation and learning during physical education courses. Fifty-three children from two first-grade classes of the high school participated in this study. Participants were dichotomized and taught using the problem-solving or traditional method. The study comprised three principal phases, namely, pre-test, treatment, and post-test (retention). The results revealed that performance for both motivation and learning obtained by the group using the problem-solving method was significantly greater to that produced by the traditional method. Therefore, these results showed the potential benefits of the problem-solving method as an efficient strategy intended for motor skills and performance enhancement, as well as motivation development during physical education courses.